Death and Destitution: The Global Distribution of Welfare Losses from the COVID-19 Pandemic - Francisco H. G. Ferreira; Olivier Sterck; Daniel Gerszon Mahler; Benoit Decerf (Institute of Labor Economics (IZA), 2021)
The Covid-19 pandemic has brought about massive declines in wellbeing around the world. This paper seeks to quantify and compare two important components of those losses – increased mortality and higher poverty – using years of human life as a common metric. We estimate that almost 20 million life-years were lost to Covid-19 by December 2020. Over the same period and by the most conservative definition, over 120 million additional years were spent in poverty because of the pandemic. The mortality burden, whether estimated in lives or in years of life lost, increases sharply with GDP per capita. The poverty burden, on the contrary, declines with per capita national incomes when a constant absolute poverty line is used, or is uncorrelated with national incomes when a more relative approach is taken to poverty lines. In both cases the poverty burden of the pandemic, relative to the mortality burden, is much higher for poor countries. The distribution of aggregate welfare losses – combining mortality and poverty and expressed in terms of life-years – depends both on the choice of poverty line(s) and on the relative weights placed on mortality and poverty. With a constant absolute poverty line and a relatively low welfare weight on mortality, poorer countries are found to bear a greater welfare loss from the pandemic. When poverty lines are set differently for poor, middle and high-income countries and/or a greater welfare weight is placed on mortality, upper-middle and rich countries suffer the most.
Keywords: D60; I15; I31; I32; 330; COVID-19; pandemic; welfare; poverty; mortality; global distribution